Popular Action As A Study Object In Thesis And Dissertations In Brazil: A Balance Of Academic Production (2010-2019) (Revista Direito em Debate, 2022)
In Brazil, the Popular Action is a constitutional guarantee, provided in 5th article, item LXXIII, and gives any citizen legitimacy in induction of the Judiciary to protect public property. The present article presents a balance of the national scientific production, specifically of the doctoral theses and master's dissertations, of the last ten years, about the Popular Action. Systematizes and analyzes, from the CAPES Catalog of Theses and Dissertations, the works that elected the institute as the central object of study and investigates how they approached it. From the data found, the analysis procedure consisted of characterizing the research based on thematic categories, in addition to explaining other information, such as the legal regime of educational institutions, distribution by geographic region and methodology used. As a main result, low academic production in relation to the theme was identified, focusing on private educational institutions in the Southeast and South of the country, and on master's courses.